Malocclusion Impact Scale for Early Childhood (MIS-EC): development and validation - Márcio Alexandre Homem; Maria Letícia Ramos-Jorge; Isabella Mota-Veloso; Tulio Silva Pereira; Paulo Antônio Martins Júnior; David Normando; Saul Martins Paiva; Isabela Almeida Pordeus; Carlos Flores-Mir; Leandro Silva Marques (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract: This study aimed to develop and validate the Malocclusion Impact Scale for Early Childhood (MIS-EC), a malocclusion-specific measure of oral health-related quality of life (OHRQoL) of children aged 3-5 years and their parents/caregivers. A pool of items was analysed to identify those relevant to the assessment of the impact of malocclusion on OHRQoL. Dental professionals and mothers of children with and without malocclusion rated the importance of these items. The final version of the MIS-EC was evaluated in a cross-sectional study comprising 381 parents of children aged 3-5 years to assess construct validity, internal consistency and test-retest reliability. Twenty-two items were identified from item pooling. After item reduction, eight items were chosen to constitute the MIS-EC, in addition to two general questions. The MIS-EC demonstrated good internal consistency (Cronbach's alpha = 0.79 for the Child Impact section and 0.53 for the Family Impact section), and excellent test-retest reliability (ICC = 0.94), floor effect was 55.7% and ceiling effect 0%. MIS-EC scores indicating worse OHRQoL were significantly associated with the presence of malocclusion (p < 0.05). The MIS-EC is reliable and valid for assessing the impact of malocclusion on the OHRQoL of preschool children and their parents/caregivers.